Fibroblast Growth Factor 2 Promotes Bladder Hypertrophy Caused by Partial Bladder Outlet Obstruction - Gao, Ye; Liu, Peilin; He, Fan; Yang, Xingliang; Wu, Ronghua; Chen, Wei; Li, Longkun; Yang, Zhenxing (Frontiers in Cell and Developmental Biology, 2021)
Noninvasive biomarkers to identify patients with bladder outlet obstruction (BOO)-related dysfunction are still needed to guide clinical practice. The current study aims to investigate molecular alterations and biomarkers associated with partial BOO (PBOO) in rats. Sprague–Dawley rats were used to establish the BOO model. Serum samples from 60 patients with benign prostatic hypertrophy (BPH) were used for ELISA analysis. RNA-seq and TMT-labeling proteomic analyses were conducted to identify molecular alterations. Masson's trichrome, H&E, and IHC staining and Western blotting were conducted by using conventional methods following the manufacturer’s instructions. Rats with PBOO experienced hypertrophy of smooth muscle cells and hyperplasia of interstitial cells during the first 4 weeks after the initiation of obstruction. Four weeks later, rats with PBOO showed activation of the adaptive immune response, cell death and apoptosis. The levels of BDNF and FGF2 in the serum gradually increased in the first four weeks and gradually decreased after week 4. FGF2 levels slightly correlated with prostate volume (R=0.156, P=0.0028) but not with age or BMI in BPH patients. No correlations were found between BDNF levels and prostate volume, age or BMI. BOO induces a change from bladder compensation to decompensation at week 4. FGF2 is involved in the development of hypertrophy in the PBOO bladder and shows a positive correlation with prostate volume in BPH patients.